Antibiotic-Resistant Genes and Polymorphisms of blaTEM1 gene in Multidrug-resistant Escherichia coli from Chicken Eggs and Cloacal Swabs in Sleman, Yogyakarta: The Impact on Public Health - Nastiti, Niken Irfa; Asmara, Widya; Putri, Khrisdiana (Indonesian Journal of Tropical and Infectious Disease, 2024)
Antimicrobial resistance in pathogenic bacteria is a serious problem in public health. Antibiotic-resistant pathogens are the cause of many deaths.  Escherichia coli (E. coli) is one of the bacteria that experienced multi-drug resistance (MDR). Infection of Escherichia coli in humans occurs through transmission of fecal-oral. This study, conducted at the Veterinary Public Health Laboratory of Gadjah Mada University, aimed to assess MDR E. coli prevalence in 200 chicken egg samples sourced from poultry farms and supermarkets, alongside 63 cloacal swab samples from broiler poultry in Sleman, Yogyakarta. The study focused on detecting resistance genes including tetA, aadA1, aph(3)IIa, and blaTEM1, also analyzing polymorphisms in the blaTEM1 gene associated with antibiotic resistance. Identification technique of E. coli positivity refers to the Indonesian National Standard (SNI) 2897:2008, then E. coli identification was performed using the Analytical Profile Index (API) Test 20E Kit. Antibiotic sensitivity was determined by the Kirby Bauer method. Detection of antibiotic resistance genes in E. coli were determine using Polymerase Chain Reaction (PCR) method. Sequencing and analysis of polymorphism and phylogenetic were performed only in blaTEM1. There were 12 samples identified as having E. coli (1 from chicken eggs and 11 from cloacal swabs), resistance percentages were highest for erythromycin (100%), ampicillin (91.7%), ciprofloxacin (91.7%), sulfamethoxazole (83.3%), streptomycin (83.3%) gentamicin (75%), tetracycline (41.7%), and chloramphenicol (25%). respectively. All of 12 E. coli samples were bacteria with MDR. Resistant genes were prevalent, notably blaTEM1 and aadA1 (100% each), with aph(3)IIa and tetA genes also detected in 58.3% of samples each. Sequencing of the blaTEM1 gene revealed polymorphisms in isolate A8. However, these did not alter its antibiotic resistance phenotype. Sequences of E. coli isolates showed similarities to strains from Vietnam, China, and India, countries with high antibiotic consumption, particularly ampicillin.